Neutrinos above the Earth's Surface - Askold Sergeevich Belyakov (Newinera Publisher, 2023)
In article “Doppler Effect and neutrino acoustic signatures”, published in the journal “LA MULTIAPP” on February 25, 2022, I was forced to touch on an astrophysical topic when, in the data stream obtained by monitoring the acoustic noise of the earth’s crust with high amplitude resolution (more 240 dB) and in a wide frequency band (from 0.1 Hz to 50 kHz) events began to appear, the forms and frequencies of which are not typical for geophysics and seismology. Similar forms can be seen in works on the detection of acoustic traces of neutrino decay in water and ice. The possibilities of increasing the sensitivity in measurements in a solid medium are discussed. In addition, underwater and underground facilities are being built that use the effect of Cherenkov radiation. All of these methods require complex and very expensive installations on a huge scale. Even acoustic measurements in water and in wells are very laborious and expensive, and most importantly: such measurements are forever tied to a specific place. Therefore, the creation of a light, compact and mobile device for recording acoustic traces of neutrino decay is an urgent task, the solution of which will allow recording traces of neutrino decay not only in water and the earth's crust, but also in air, into space, on planets and satellites.